Influence of lateral position and pneumoperitoneum on oropharyngeal leak pressure with two types of laryngeal mask airways. Issue 9 (25th July 2017) - Lan, S.; Zhou, Y.; Li, J. T.; Zhao, Z. Z.; Liu, Y.
Abstract : Background: An important parameter to monitor adequate ventilation for laryngeal mask airway (LMA) is its oropharyngeal leak pressure (OLP). This study was designed to evaluate and compare the effect of lateral position and pneumoperitoneum on the OLP and ventilation efficiency between LMA™ Proseal (PLMA) and LMA™ Supreme (SLMA). Methods: Patients were randomized to receive either the PLMA or the SMLA. The OLP was assessed in both the supine position and the lateral position with or without pneumoperitoneum. Minute ventilation was increased to maintain normal EtCO2 as far as possible. Ventilatory efficiency was scored as Class I (optimal, EtCO2 35–45 mmHg), Class II (suboptimal, EtCO2 45–55 mmHg) and Class III (poor, EtCO2 >55 mmHg). Adverse events associated with LMA such as blood staining on the mask and sore throat were also recorded. Results: Within each group, the OLP was higher in the supine position than that in the lateral position with or without pneumoperitoneum ( P < 0.01). However, pneumoperitoneum did not further decrease the OLP. The OLP with PLMA was higher compared with SLMA regardless of the position and pneumoperitoneum ( P < 0.05 or 0.01). There was no significant difference in the number of patients in Class I/II/III for ventilation scores in the lateral position with pneumoperitoneum (83/7/2 in PLMA group and 76/14/2 in SLMA group, respectively). The incidence of adverse events was comparable in both groups. Conclusion: Our data demonstrate that the PLMA has a higher OLP in comparison with the SLMA in the lateral position for laparoscopic surgery. Both devices provide comparably adequate ventilatory efficiency.